Verification of deflections and cracking of RC flat slabs with numerical and analytical approaches. (1st June 2023) - Ravasini, Simone; Vecchi, Francesca; Belletti, Beatrice; Muttoni, Aurelio
Highlights: Investigation of long-term effects on displacement and cracking of RC flat slabs. Finite element modelling and analytical prediction of long-term displacements and cracking of RC flat slabs. Validation of the numerical and analytical approaches with experimental tests. Calculation of a simplified multiplicative coefficient to obtain long-term deflections. Abstract: The Serviceability Limit States ( SLS ) of reinforced concrete structures, where cracking and deflection limits are verified in the design process, are directly related to time-dependent properties of concrete. In this study, the effects of creep and shrinkage of concrete, implemented in a Finite Element Model for Non-Linear Analysis, are in-deeply investigated for reinforced concrete flat slabs at SLS and used as basis for the development of an analytical framework. In particular, the paper focuses on: (i) the description of the FE model, (ii) the comparison between the numerical and experimental results of some reinforced concrete ( RC ) flat slab tests from literature characterized by different mechanical properties, span-to-depth ratios, boundary conditions and loading histories and (iii) the development of an analytical framework for the evaluation of long term-term deflections and crack openings in hogging regions of flat slabs near columns. Based on the findings, useful insights for the evaluation of the long term-term deflections and crack opening in the context of Serviceability Limit States are provided for practical purposes.